“Everything Will Be OK”: Busking, Well-Being, and the Value of Music in Times of Pandemic - Ptatscheck, Melanie (MUSICultures)

(untitled) (Canadian Society for Traditional Music / La Société canadienne pour les traditions musicales, 2024)
Busking can produce positive atmospheres in public spaces through diverse social relations that, in addition to the music itself, can contribute to a sense of wellbeing among the urban populace. The COVID-19 pandemic highlighted the value of music and live performances in terms of their positive impact on well-being. This article analyzes the situation of buskers during the pandemic and gives insight into their subjective realities. Using the example of New York musician Colin Huggins, known as “the piano man of Washington Square Park,” the author highlights buskers’ dependence on governmental and societal support to sustain both well-being and music cultures in public spaces.